Zeolites Effects in Physical Characteristics of Low-Density Polyethylene (LDPE) and Polypropylene (PP) Pyrolysis into Liquid Fuel - Elsa Meilia Mayora; Arifin Arifin; Putranty Widha Nugraheni (Universitas Diponegoro, 2024)
The decline in the quality of waste management has generally started to occur since the prolonged economic crisis in Indonesia. Plastic waste includes inorganic waste, which is currently widely used by industry and households. Therefore, it is necessary to have an alternative recycling process, like converting plastic waste into liquid fuel. The research objective is to utilize LDPE plastic waste (Low-Density Polyethylene) and PP (Polypropylene)in liquid fuelutilizing pyrolysisto determine the effect of using a zeolite catalyst by comparing the results of the pyrolysis process. The investigation took place at the Wonosari landfill in Singkawang, where parameters such as density, viscosity, and color were examined. The pyrolysis results underwent consistency testing through the Mann-Whitney test. According to the study findings, the average physical parameter values for viscosity and density of LDPE pyrolysis liquid fuel were 0.302 cP, LDPE+catalyst was 0.114 cP, with densities of 767 kg/m3 and 737 kg/m3. For PP, the average viscosity was 2.812 cP, and PP+catalyst was 0.248 cP, with densities of 774 kg/m3 and 735 kg/m3. Samples of PP and LDPE with catalysts exhibited lower density values compared to those without catalysts.